Pengaruh Literasi Keuangan, Financial Self-Efficacy, dan Persepsi Risiko Terhadap Minat Penggunaan Pinjaman Online pada Gen Z Pulau Sumbawa - Azril Nuraqsya Prana; Hartini Hartini (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2026)
The rapid development of financial technology has driven an increase in the use of online loans among Generation Z, although these services also carry various risks. This study aims to analyze the influence of financial literacy, Financial Self-Efficacy, and risk perception on the interest in using online loans among Generation Z on Sumbawa Island using a quantitative approach through a survey and multiple linear regression analysis. The results show that, both partially and simultaneously, all three variables have a significant negative effect and account for 22.8% of the variation in interest in using online loans. These findings confirm that improved financial literacy, confidence in managing finances, and risk awareness can reduce interest in using online loans, highlighting the need for ongoing financial education to encourage wiser financial decisions.